Interaction of the European Union: the Genesis of integration (International relations and international law Journal, 2019)
The article deals with the history of integration processes in Europe that led to the creation of the European Union. The authors consider the Genesis of European integration, starting with the formation of the European coal and steel community. The article presents a historical approach to the analysis of the political development of the European Union, in particular, focuses on the special historical context of the emergence of the ERUs, shows the process of transformation of the EU institutions, as well as its modern problems. Integration processes affect and modify all spheres of international relations. The growing interdependence of the world and the emergence and exacerbation of global problems have increased the need to strengthen multilateral cooperation and have contributed to the expansion of its territory and, consequently, integration. The defining stage in the research of the main trends of European integration can be considered work in line with the fundamental theories of European integration, primarily federalism, functionalism, neofunctionalism and others. We emphasize that when analyzing the historical aspects of the integration processes in Europe, the authors focused on the works of famous scientists who were developing the theoretical foundations of integration. With the identification of forms and patternsof integration, the essence of integrating factors and disintegrating trends, with the understanding of thefeatures and prospects of the real processes of cooperation of States associated scientific understandingof the problems of integration.Key words: European Union, integration, European coal and steel Union, Jean Monet, Lisbon Treaty.